2020
DOI: 10.1039/c9np00066f
|View full text |Cite
|
Sign up to set email alerts
|

Natural products as modulators of eukaryotic protein secretion

Abstract: Covering: up to the end of 2019 Diverse natural product small molecules have allowed critical insights into processes that govern eukaryotic cells' ability to secrete cytosolically synthesized secretory proteins into their surroundings or to insert newly synthesized integral membrane proteins into the lipid bilayer of the endoplasmic reticulum. In addition, many components of the endoplasmic reticulum, required for protein homeostasis or other processes such as lipid metabolism or maintenance of calcium homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 157 publications
1
48
0
Order By: Relevance
“…73 Other natural Sec61 blockers have been identified, which inhibit protein translocation by targeting a partially overlapping site in the pore-forming Sec61α subunit. 94 Interestingly, the mutations conferring resistance to mycolactone clustered in the same region, 73 suggesting that structurally different Sec61α inhibitors share a common binding site and mode of action. Gérard et al 95 recently reported an electron cryo-microscopy structure of mycolactone bound Sec61α.…”
Section: F I G U R Ementioning
confidence: 99%
“…73 Other natural Sec61 blockers have been identified, which inhibit protein translocation by targeting a partially overlapping site in the pore-forming Sec61α subunit. 94 Interestingly, the mutations conferring resistance to mycolactone clustered in the same region, 73 suggesting that structurally different Sec61α inhibitors share a common binding site and mode of action. Gérard et al 95 recently reported an electron cryo-microscopy structure of mycolactone bound Sec61α.…”
Section: F I G U R Ementioning
confidence: 99%
“…1 A), hijack the host cell secretory pathway to correctly synthesise, fold and assemble important viral proteins ( Bojkova et al, 2020 ; Gordon et al, 2020 ; Sicari et al, 2020 ). Hence, small molecule inhibitors of Sec61-mediated co-translational protein entry into the endoplasmic reticulum (ER) ( Luesch and Paavilainen, 2020 ) have potential as broad-spectrum antivirals ( Heaton et al, 2016 ; Shah et al, 2018 ). Such inhibitors offer a dual approach: first, by directly inhibiting production of key viral proteins and, second, by reducing levels of host proteins co-opted during viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…1A), hijack the mechanisms of host secretory pathway-mediated protein synthesis in order to correctly synthesise, fold and assemble important viral proteins (Bojkova et al, 2020; Gordon et al, 2020; Sicari et al, 2020). Hence, small molecule inhibitors of Sec61-mediated co-translational protein entry into the endoplasmic reticulum (ER) (Luesch and Paavilainen, 2020) have recently attracted attention as potentially broad-spectrum antiviral agents (Heaton et al, 2016; Shah et al, 2018). Such inhibitors offer a dual approach to reduce viral pathogenicity; first, by directly inhibiting the production of key viral proteins and, second, by reducing the levels of host proteins that are co-opted during viral infection.…”
Section: Introductionmentioning
confidence: 99%